Computer assisted zygomatic implants in atrophic maxilla: a clinical report - Miranda, Paula Roberta Pires; Campos, Júlio Ferraz; Leite, Samir de Moura Gonçalves; Ribeiro, Nathalia de Carvalho Ramos; Silva, Robson Roberto da; Nishioka, Renato Sussumu (Brazilian Dental Science, 2026)
Different bone anchorage techniques allow the rehabilitation of atrophic maxillae without the need for bone reconstructions techniques, the zygomatic implant is one of the therapeutic options. The present case reports the use of computer assisted zygomatic implants to rehabilitate an atrophic maxilla. The surgery was planned using a planning software, with the use of .stl and .dicom archives obtained from the patient mouth scanning and cone beam tomography. Four zygomatic implants were planned, along with a drill guide and a prototype, which were printed. Surgery was trained in the prototype, then was performed with local sedation of the patient. A protocol-type prosthesis was installed within 24 hours. The chosen technique proved to be effective in an 12-month follow-up, during which the implants showed no mobility, the prosthesis showed no prosthetic compensations and the patient had no complaints.KEYWORDSAtrophic maxilla; Case reports; Computer-assisted implant surgery; Implant; Zygomatic implant